Treatment of periodontal disease improves glycaemic control in Type-1 and Type-2 diabetics: a literature review - Sultan, Ahmed; Patel, Fathima (Trinity Student Medical Journal, 2012)
Periodontal disease and diabetes mellitus are both complex chronic diseases that have a bidirectional intrinsic link. It has been suggested that the chronic inflammation and infection of pre-existing periodontal disease may impair glycaemic control and hasten the development of diabetic complications. Conflicting results have been shown by the limited number of short-term randomised controlled studies carried out to ascertain whether the treatment of periodontal disease contributes to improvement of glycaemic control. High quality reviews have concluded that small but significant improvements can be expected. Glycated haemoglobin (HbA1c), a haemato- logical indicator of hyperglycaemia, is noticeably reduced in Type-2 diabetics who undergo routine scaling/root planing and oral hygiene regimens when compared to such individuals with no periodontal treatment interventions. Regular and appropriate periodontal therapy leading to any improvement in glycaemic control has the potential to make a significant impact on the quality of life for diabetic patients. The aim of this re-view is to discuss the literature supporting these arguments.